Identification of Quantitative trait Loci for Resistance to White-Backed Planthopper (Sogatella furcifera) in Rice with Milyang 46 (Cheongcheongbyeo) Background (The Philippine Journal of Crop Science, 2013)
White-backed planthopper (WBPH) is a new emerging migratory insect pest in Korea. The potential threat of WBPH is critical for japonica cultivars, and prediction of occurrence is difficult because of their migratory behavior. Improving WBPH resistance of new rice cultivars in Korea is important before major damage due to this pest occurs. The study was conducted to identify the quantitative traits loci (QTLs) associated with WBPH resistance in rice. The QTL associated with resistance to WBPH was determined using 94 doubled haploid (DH) lines derived from Korean rice, Cheongcheongbyeo and Nagdongbyeo. WBPH resistance was evaluated through resistance score and seedling mortality which ranged 0.5-9.0 and 0-95.5%, respectively. The WBPH resistance showed continuous distribution among DH population. Five QTLs associated with WBPH resistance were determined and mapped on chromosome 2, 6 and 11. The linkage map comprised of 143 sample sequence repeats, which covered 1012.4 cM with an average interval of 8.1 cM. Three QTLs conferring resistance score to WBPH , namely qwbph2b, qwbph6d, and qwbph11 were found in the regions of RM2770-RM12532, RM527-RM528 and RM4469-RM26981 on chromosomes 2,6 and 11. These QTLs explained 56% of the total phenotypic variance detected by the resistance score. On the other hand, two QTLs qwbph2c and qwbph6e conferring seedling mortality were identified and were overlapping with qwbph2b and qwbph6d. The QTLs were responsible for 31% of the total phenotypic variance scored by seedling mortality. Thus, qwbph2b and qwbph6d are major and stable QTL for WBPH resistance.